School of jolly boys, The - Truman State University, Pickler Memorial Library Special Collections and Museums (Owner, Digitizing Technician); Sims Song Slide Collection (Sims Song Slide Corporation (Kirksville, Mo.), 2024)
Songs; Scores; Glass lantern slide depicting score of "School of Jolly Boys."